KAJIAN ASPEK SDM PERUSAHAAN, DAMPAK SOSIAL DAN EKONOMI MASYARAKAT DALAM MENUNJANG KEBERLANJUTAN PABRIK KELAPA SAWIT (PT. DDP LUBUK BENTO MUKOMUKO) - Auliya Rahma Dhita; Damres Uker; Wuri Marsigit (Jurnal Agroindustri, 2022)
Communities around PT. Darian Dharma Patama works as an employee at the company, manages his oil palm plantation, and trades. Local community work before PT. Darian Dharma Pratama stood, namely gardening and farming. The development of palm oil mills has positive and negative impacts on the community around the location of PT. DDP Lubuk Bento Mukomuko. This study aims to determine the palm oil mill based on aspects of the company's human resources, social and economic impact of the community around the location. This research uses trigulation technique combining primary and secondary data collection. In this study using random sampling and sampling in this study using the possibility of sampling with simple random sampling that is taking randomly from the population. The data comes from the form of numbers but from interviews with informants and official company documents. This type of research uses descriptive research with facts and correct interpretation, by studying the data obtained through interviews and company documents, regarding the activities that exist in the company, the relationship between the company and the community. The results of this study PT. Darian Dharma Pratama Lubuk Bento in the aspect of company human resources, namely implementing an SOP system in the form of companies providing training and development to employees. While the results of the company's Social Impact are providing assistance in the form of CSR to the community and the economic impact of the community, namely the company providing job opportunities to be able to change the standard of living of the community. Therefore PT. Darian Dharma Pratama can be said to be sustainable in terms of Human resources Aspects, Social Impacts and Economic Impacts on the community around the factory location.